Vista for educational and research activities in humanitarian and socio-economic disciplines in presence of a non-profile faculty in university - M. S. Novikov; S. V. Novikov (Омский научный вестник: Серия "Общество. История. Современность")
From the organization of non-profile faculties in agricultural, technical and other universities, the Ministry of Science and Education of the Russian Federation has refused. Meanwhile, the experience of Humanities Faculty, Faculty of Economics, Faculty of Law need to be generalized and used. The authors of the article, who had the experience of teaching and working in the non-profile faculty, consider that the rejection of this practice had a negative impact on students and the level of teaching